THE HISTORY OF TRADITIONAL CLOTHING OF THE KAJANG COMMUNITY, BULUKUMBA DISTRICT (COMMUNICATION ETHNOGRAPHIC STUDY): Sejarah Pakaian Tradisional Komunitas Kajang, Kabupaten Bulukumba (Studi Etnografis Komunikasi) - Simahdi (Jurnal Diskursus Islam, 2025)
This research was conducted in Tanah Toa Village, Kajang District, Bulukumba Regency, South Sulawesi, which until now still adheres to the beliefs of its ancestors, one of which is wearing all-black clothes which are considered sacred and sacred. This research method is descriptive qualitative and uses an ethnographic communication approach. Data was collected by means of observation, interviews, literature and documentation. The purpose of this study was to describe the history and traditions of the Ammatoa Kajang ethnic community’s traditional clothing, Bulukumba Regency. The results of this research on the history and traditions of the Kajang tribe’s traditional clothing are a marker of the cultural identity of the Ammatoa ethnic community, which illustrates the belief that humans are born from the realm of darkness until the end of their lives they also return to the realm of darkness. Carrying out the Ammatoa ancestral tradition as the highest customary leader who also used traditional clothing in the past, reflecting adherence to customary law (Pasang) especially the principle of attallasa’ kamase-mase or living modestly/simplely, representing equality for everyone before God (Turiek Akra ’na), a sense of equality and a shared destiny.